A dichotomy of smokers in the Philippines following sin tax reform: Distinguishing potential quitters from those unlikely to quit - Kent Jason Go Cheng; Miguel Antonio Garcia Estrada (PLoS ONE, 2022)
The Philippine government significantly raised cigarette excise taxes in 2013, following passage of the landmark Sin Tax Reform Act of 2012. As a result, cigarette prices increased substantially. Given varying smokers’ responses to the price increase, we examined underlying typologies of Filipino smokers and assessed how these typologies determine smoking intensity. We used cross-sectional data from the 2015 wave of the Philippine Global Adult Tobacco Survey (N = 1,651). To uncover typologies, random effects latent class modelling was used on six individual smoker responses (attempting to stop, thinking about quitting, decreasing sticks smoked, switching to cheaper brands, buying in bulk, and asking from others). Bivariate and multivariate analyses were employed to uncover determinants of typologies and smoking intensity. We found two typologies based on smokers’ response. The first group, called “potential quitters” (62.62%), is composed of smokers who are more likely to consider quitting and decrease sticks smoked. The second group, called “unlikely to quit” (37.38%), have smokers who opt for price-minimization strategies like switching to cheaper brands, buying in bulk, or asking cigarettes from others. Potential quitters tend to be female, a student, and less nicotine dependent. They smoke up to three fewer sticks than those unlikely to quit, controlling for other factors. Nicotine dependence stood out as the most important predictor of being in the unlikely to quit group. The dominant role of nicotine dependence in determining a smoker’s typology points to the need for non-price based measures, such as those targeted towards highly-nicotine dependent smokers, to complement tax-induced price increases and comprehensively address the smoking problem.